Impact of Agricultural Sector Investments on Income Distribution and Poverty in Central Sulawesi, Indonesia - Rustam Abd. Rauf; Arief Daryanto; D. S. Priyarsono (AGROLAND The Agricultural Sciences Journal (e-Journal), 2017)
Central Sulawesi is a province in Indonesia with abundant natural resources particularly in agricultural sector. This condition suggests that the agricultural sector plays a very significant role in Central Sulawesi economy. One of the causal factors leading to the disparity of income distribution and poverty is investment allocation with its inconsistency occurs in sectoral development planningThe Gini Ratio of Central Sulawesi Province was 0.4844 in 2008 reflecting moderate level of income disparity for the income distribution among household groups. Simulation of increasing investment on agricultural and other sectors for 10% can generally decrease poverty at all groups of households both in rural and urban area. Simulation 2 (investment in plantation subsector) led to highest poverty decline as comparison to other simulation.